Dysgermgerminoma in a 14 year old girl: a case report - Kurude, V. N.; Thorat, Sukanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
An accurate diagnosis of ovarian dysgerminoma is crucial as, as its management differs from other ovarian tumours. We report a case of ovarian dyegerminoma in a 14 year old girl who presented with abdominal distention. Examination revealed a huge intra-abdominal mass causing displacement of bowel loops laterally. On ultrasound, a solid heterogeneously hyperechoic lesion of size 18 x 9.4 cm with few cystic and necrotic areas within most likely, left adnexa reaching upto the umbilicus and shows vascularity within both ovaries not seen separately from the lesion. On CT (A+P), a heterogenous hypodense polycystic mass of size 8.5x1.4x16.7 with multiple irregular hypodensities seen in the lower abdomen and pelvis. The mass was removed after laparotomy under general anaesthesia. Finally, the diagnosis of ovarian germ cell tumor (Dysgerminoma was made. Present case presented with marked abdominal distention, without any loss of weight, appetite or any menstrual problem. Such a presentation may be unusual for such a large malignant ovarian mass.